2010
DOI: 10.3390/v2010131
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing and its Control in Hepatitis Delta Virus Replication

Abstract: The hepatitis delta virus genome is a small circular RNA, similar to viroids. Although HDV contains a gene, the protein produced (HDAg) is encoded by less than half the genome and possesses no RNA polymerase activity. Because of this limited coding capacity, HDV relies heavily on host functions and on structural features of the viral RNA—very much like viroids. The virus’ use of host RNA editing activity to produce two functionally distinct forms of HDAg is a particularly good example of this reliance. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…The higher efficiency observed in Fig. 1B compared to the previous study is likely due to sequence changes, including editing at the amber/W site (28) in the serum-derived RNA that could decrease the efficiency of replication (17), although the choice of ends for the linear RNA could also contribute (27). Regardless, the in vitro-synthesized circular RNA provides a highly effective method for initiating replication using small amounts of RNA with homogeneous sequence and does not require template switching (22,23) events to initiate replication.…”
Section: Efficient Initiation Of Hdv Replication In Cultured Cells Bycontrasting
confidence: 62%
“…The higher efficiency observed in Fig. 1B compared to the previous study is likely due to sequence changes, including editing at the amber/W site (28) in the serum-derived RNA that could decrease the efficiency of replication (17), although the choice of ends for the linear RNA could also contribute (27). Regardless, the in vitro-synthesized circular RNA provides a highly effective method for initiating replication using small amounts of RNA with homogeneous sequence and does not require template switching (22,23) events to initiate replication.…”
Section: Efficient Initiation Of Hdv Replication In Cultured Cells Bycontrasting
confidence: 62%
“…R1, R2 = ribozyme domain; C = C-terminal amino acid extension; A = PolyA. HDAg: hepatitis delta antigen; E = RNA editing site (position at nt 1015) [ 38 ]. Numbering is according to HDV strain NC1001653.…”
Section: Resultsmentioning
confidence: 99%
“…HDAg is expressed in two isoforms, small (SHDAg) and large (L-HDAg). S-HDAg is required for the replication of HDV, while L-HDAg inhibits viral replication and is required for the envelopment of the HDV genomic RNA by hepatitis B virus proteins [123] . Bell et al [124] found that over half of the L-HDAg domains were localized beside ND10.…”
Section: Rna Virusesmentioning
confidence: 99%